Structural system identification by measurement error‐minimizing observability method. Issue 10 (26th July 2019) - Lei, Jun; Lozano‐Galant, Jose Antonio; Xu, Dong; Turmo, Jose
Summary: This paper proposes a method for the finite element model updating using static load tests under the framework of observability analysis. Previous works included measurement errors in the coefficient matrix of the observability equations. This impeded the obtainment of accurate estimations. To deal with this issue, the proposed method relocates the errors and incorporates an optimization procedure to minimize the square sum of these errors. This method is able to identify the structural parameters of complex structures where the axial and bending behaviors are coupled, such as inclined beams or frame structures. Its application is illustrated by three structures. First, the method was validated in a beam‐like structure by comparing it with other methods in the literature. Then the effects of different factors were investigated in a multistory frame and a rigid frame bridge with inclined piers. These factors include the curvatures, the inclusion of rotation measurements, and the constraints on the range of unidentifiable parameters. The importance of rotation measurements is demonstrated in static structural system identification.